Inovasi Latihan Rondo: Meningkatkan Kemampuan Passing Tim Futsal - Zainuddin, M Said (Indonesian Journal of Physical Activity, 2024)
Improving passing ability is an important aspect in futsal games. This study examines the effectiveness of the rondo training model in improving the passing ability of the SMK Negeri 10 Makassar futsal team. The research method used a one group pretest-posttest experimental design involving 20 students as samples. Data were analysed with paired sample t test. The results showed that the rondo training model had a significant effect on improving passing skills (p<0.05). The calculated t value (7.353) is greater than the t table value (1.729) and the significance value is smaller than 0.05 (0.000 <0.05). The rondo training model provides an increase in passing ability by 16.3%. This study concludes that the rondo training model is effective in improving the passing ability of the futsal team. This training model can be used as an alternative for coaches to improve the performance of the futsal team.